2013
DOI: 10.1080/1747423x.2013.786149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forest conversions to oil palm plantations on freshwater macroinvertebrates: a case study from Sarawak, Malaysia

Abstract: Oil palm plantations in Malaysia are expanding rapidly due to global oil and biofuel demand. This is of particular concern, as the conversion process of forested land to oil palm plantations and the maintenance of a plantation can significantly alter freshwater ecosystems. This is a result of the initial loss of a forested catchment, particularly the riparian vegetation, changes to the bed and banks of streams, sedimentation and changes to detrital inputs. In addition, various chemicals used on the plantations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 23 publications
2
41
0
5
Order By: Relevance
“…Se han documentado diversos efectos de este cultivo, como el impacto en la pĂ©rdida de biodiversidad, al reemplazar zonas de bosque primario y de alto valor ecolĂłgi-co [4,5]; efectos en la poblaciĂłn de macroinvertebrados en cuerpos de agua dulce [6], o potenciales impactos de sus emisiones en la calidad del aire [2,7].…”
Section: Distrito Metropolitano De Quito (Dmq)unclassified
“…Se han documentado diversos efectos de este cultivo, como el impacto en la pĂ©rdida de biodiversidad, al reemplazar zonas de bosque primario y de alto valor ecolĂłgi-co [4,5]; efectos en la poblaciĂłn de macroinvertebrados en cuerpos de agua dulce [6], o potenciales impactos de sus emisiones en la calidad del aire [2,7].…”
Section: Distrito Metropolitano De Quito (Dmq)unclassified
“…In addition, low abundance of aquatic insects could be resulted from high concentrations of suspended sediment, which is a significant factor in determining the complexity of food web and consequently reflected the effect of pollution (Yule et al 2010). In selected rivers in Kuching, Sarawak, lower abundance and diversity of aquatic insects was found in oil palm plantations, compared to primary forest, which could be resulted from high concentration of suspended sediment and pesticide contamination (Mercer et al 2013).…”
Section: Distribution and Diversity Of Aquatic Insects Communitymentioning
confidence: 99%
“…Various ecological studies have highlighted the relationship between water quality and aquatic insects in Malaysia (Mohd. Rasdi et al 2012;Wahizatul et al 2011;Yap & Rahim 2011), while some of the recent studies reported: Effects of land use changes to aquatic insects (Al-Shami et al 2011;Che Salmah et al 2013;Jinggut et al 2012;Mercer et al 2013); seasonal variations of Ephemeroptera, Plecoptera and Trichoptera (EPT) (Suhaila et al 2012) and influence of canopy cover and substrate embeddedness to EPT distribution (Suhaila & Che Salmah 2014). However, to date, there is still a huge gap in the knowledge of aquatic insects and ecological understanding of the tropical streams (Al-Shami et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations